Sperm Proteome after Interaction with Reproductive Fluids in Porcine: From the Ejaculation to the Fertilization Site - Luongo, Chiara (Int J Mol Sci, 2020)
Ejaculated sperm are exposed to different environments before encountering the oocyte. However, how the sperm proteome changes during this transit remains unsolved. This study aimed to identify proteomic changes in boar sperm after incubation with male (seminal plasma, SP) and/or female (uterine fluid, UF; and oviductal fluid, OF) reproductive fluids. The following experimental groups were analyzed: (1) SP: sperm + 20% SP; (2) UF: sperm + 20% UF; (3) OF: sperm + 20% OF; (4) SP + UF: sperm + 20% SP + 20% UF; and (5) SP+OF: sperm + 20% SP + 20% OF. The proteome analysis, performed by HPLC-MS/MS, allowed the identification of 265 proteins. A total of 69 proteins were detected in the UF, SP, and SP + UF groups, and 102 proteins in the OF, SP, and SP + OF groups. Our results showed a higher number of proteins when sperm were incubated with only one fluid than when they were co-incubated with two fluids. Additionally, the number of sperm-interacting proteins from the UF group was lower than the OF group. In conclusion, the interaction of sperm with reproductive fluids alters its proteome. The description of sperm-interacting proteins in porcine species after co-incubation with male and/or female reproductive fluids may be useful to understand sperm transport, selection, capacitation, or fertilization phenomena.